Russian–Belarusian Energy Cooperation. Issue 6 (2nd June 2016) - Bolkunets, D.V.
Abstract : This article examines the current state of Belarus's energy system, as well as the relationships among Belarus, Kazakhstan, and Russia under the Customs Union and the Single Economic Space. The development of new ideas for energy security that would significantly reduce the effect of hydrocarbon exports on economic development and increase the national economy's competitiveness are necessary. The creation of a common energy market under the Eurasian Union should be the foundation of this process.